A case series of multidrug‐resistant tuberculosis in renal transplant recipients: Challenges in management from a TB endemic country. Issue 4 (17th June 2021) - Babar, Zaheer Udin; Nasim, Asma; Kumar, Sunil; Nazmi, Jawwad; Badlani, Sanjay; Nadeem, Ali; Aziz, Tahir
Abstract: Multidrug‐resistant tuberculosis (MDR‐TB) is caused by Mycobacterium tuberculosis that is resistant to isoniazid and rifampicin (Rif). The use of immunosuppressive drugs in solid organ transplant recipients can increase the risk of TB. Management of MDR‐TB is quite challenging in the general population with poor compliance owing to lengthy treatment duration and drug toxicities. New drugs as well as shorter regimen have been used to increase the likelihood of adherence. The experience of treating MDR‐TB in the transplant recipients is limited. New drugs like bedaquiline, linezolid, clofazimine, and delamanid have rarely been used in transplant recipients. To the best of our knowledge, only 14 cases of MDR‐TB in transplant population have been reported in the literature and no case from Pakistan, a high TB burden country. We are reporting our experience of treating 4 renal transplant recipients. We used new drug regimen and found many side effects. Treatment outcome was successful with complete cure in 3 of our patients, however one died of severe drug toxicity. The most worrisome drug interaction was between azathioprine and linezolid, with life‐threatening thrombocytopenia. There was no graft dysfunction noted at the end of the therapy. The management of MDR‐TB in transplant recipients is challenging; excellent coordination between transplant team and Infectious Diseases Physician for close monitoring and follow‐up is needed.